Selective memory and digital representation: Chinese Indonesians in ANRI’s “Today’s Archives” virtual exhibition - Eritrina Putri Ekantari; Lasiyo Lasiyo; Budiawan Budiawan (Center for Sociological Studies and Community Developmen, 2026)
“Today’s Archives” is a virtual archival exhibition organized by the National Archives of the Republic of Indonesia (ANRI) that presents historical events and archival materials related to Indonesian society, including Chinese Indonesians. This study examines how a state organized virtual exhibition constructs public memory about Chinese Indonesians through digital archival representation. Adopting a critical paradigm and multimodal discourse analysis based on Gunther Kress and Theo van Leeuwen, the study analyzes how visual and textual elements construct meaning within digital platforms. This research contributes to digital memory and archival studies by examining how institutional curation and digital mediation shape representations of minority history in contemporary Indonesia. The findings reveal that representations of Chinese Indonesians in the “Today’s Archives” exhibition are shaped through archival selection, visual framing, captions, and platform-based narration. The exhibition predominantly emphasizes narratives of harmony, cultural visibility, and social contribution, while experiences of discrimination, political exclusion, and historical violence remain largely absent. These representations construct a selective and depoliticized form of public memory that aligns with broader narratives of multicultural harmony in post authoritarian Indonesia.